Pengaruh Kunjungan Wisatawan, Retribusi Obyek Wisata dan PHR Terhadap PAD Kabupaten Gianyar - Pertiwi, Ni Luh Gde Ana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
The objective of this research was to know the influence of total of tourists visit, tourism objects retribution income, hotel and restaurants tax to the Regional Native Income in Gianyar regency. The data used in this research was secondary data which then was analyzed by using linier doubled regression method. The result of this research showed that the total of tourists visit, tourism objects restribution income, hotel and reataurants tax significantly influenced to the Regional Native Income in Gianyar regency in estimate year 1993-2013. Regional government was suggested to add more tourism objects and the facilities and treatment to them. In collecting retribution and data collection of the total of hotel and restaurants tax also needed to be improved in order to provide leakage tax . Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: total of tourists visit; tourism objects retribution income; hotel and restaurants tax; Regional Native Income